(untitled) (Nigerian Journal of Pharmaceutical Research, 2021)
Background: ChromolaenaodorataLinn. (Asteraceae)is being used traditionally for its many medicinal properties including lowering of blood glucose level. However, few and inconsistent information about its antidiabetic potential is available. Objective: to standardize; determine physicochemical and elemental parameters; and evaluate anti-diabetic potential of ChromolaenaodorataLinn. (Asteraceae) powdered leaves in alloxan-induced diabetic rats. Materials and Methods: Physicochemical screening of fresh and powdered leaves of C. odorata leaves were respectively determined using a light microscope connected to a standard camera. Elemental analysis was done using Atomic Absorption Spectrometer (AAS) GBC Avanta Model. Thirty-three wistar rats of either sex weighing 150 – 200 g were used in the procedures. Acute toxicity assessment (LD50) was carried out using the guideline of Organization for Economic Cooperation and Development (OECD). Chromolaena odorata powdered leaves were evaluated using alloxan-induced model. Results: Physicochemical screening of the fresh and powdered leaves confirmed the pharmacognostic parameters of Chromolaena odorata. The moisture content was 6.0 ± 0.07 %, the alcohol soluble extractive was 30 ± 0.05 %. while the water-soluble extractive was 40 ± 0.05%. The elemental analysis of the powdered leaves of C. odorata showed that the leaves contains 29.00mg/L of K, 13.500mg/L of Na, 0.15mg/L of Mn, 4.78mg/L of Mg and 0.30mg/L of Ca. Chromolaena odoratashowed no toxicity when it was orally administered to rats (LD50 ≥ 2000 mg/kg). The powdered leaves of Chromolaena odorata at 100, 200 and 300 mg/kg showed dose and time-dependent anti-diabetic activities. Conclusion: The powdered leaves of Chromolaena odorata is non-toxic and preliminary data showed its anti-diabetic potential possibly due to the presence of some phytochemicals and mineral elements identified